Development of Android-Based Augmented Reality Learning Media Class X SMK Penda 3 Jatipuro - Keken Kusuma Prihantoro; Endar Suprih Wihidayat; Nurcahya Pradana Taufik Prakisya (Informatics Education Department, Faculty of Teacher Training and Education, Universitas Sebelas Maret, 2024)
In learning Chemistry at SMK Penda 3 Jatipuro has a limited time and only focuses on textbooks. Interactive learning media based on android technology is needed to help the learning process which can be done as an additional activity outside of class hours. Learning materials must also be projected in 3D form to facilitate students' understanding. The purpose of this study is to develop android-based augmented reality learning media for class X chemistry subjects of SMK Penda 3 Jatipuro, and find out the feasibility of this learning media for users to use. The research method used in this study is Reasearch and Development with 3 stages, namely the preliminary stage, the development stage, and the feasibility test stage. The preliminary stage is through interviews and literacy studies. At the development stage using the Prototype development method. The latter is the due diligence stage using the due diligence of media experts, material experts, and users. From this research, an android-based augmented reality-based learning media software for class X chemistry subjects for SMK Penda 3 jatipuro was obtained. From this study, this learning media obtained the feasibility test results of media experts 88%, for the feasibility test of material experts 89%, and for user feasibility tests obtained results of 78%. It can be concluded that this learning media is included in the category of feasible to use based on the scale of testing used.